Differences in microphysical properties of cirrus at high and mid-latitudes - E. De La Torre Castro; E. De La Torre Castro; E. De La Torre Castro; T. Jurkat-Witschas; A. Afchine; V. Grewe; V. Grewe; V. Hahn; V. Hahn; S. Kirschler; S. Kirschler; M. Krämer; et al. (Atmospheric Chemistry and Physics, 2023)
Despite their proven importance for the atmospheric radiative energy budget, the effect of cirrus on climate and the magnitude of their modification by human activity is not well quantified. Besides anthropogenic pollution sources on the ground, aviation has a large local effect on cirrus microphysical and radiative properties via the formation of contrails and their transition to contrail cirrus. To investigate the anthropogenic influence on natural cirrus, we compare the microphysical properties of cirrus measured at mid-latitude (ML) regions (<60∘ N) that are often affected by aviation and pollution with cirrus measured in the same season in comparatively pristine high latitudes (HLs; ≥60∘ N). The number concentration, effective diameter, and ice water content of the observed cirrus are derived from in situ measurements covering ice crystal sizes between 2 and 6400 µm collected during the CIRRUS-HL campaign (Cirrus in High Latitudes) in June and July 2021. We analyse the dependence of cirrus microphysical properties on altitude and latitude and demonstrate that the median ice number concentration is an order of magnitude larger in the measured mid-latitude cirrus, with 0.0086 cm−3, compared to the high-latitude cirrus, with 0.001 cm−3. Ice crystals in mid-latitude cirrus are on average smaller than in high-latitude cirrus, with a median effective diameter of 165 µm compared to 210 µm, and the median ice water content in mid-latitude cirrus is higher (0.0033 g m−3) than in high-latitude cirrus (0.0019 g m−3). In order to investigate the cirrus properties in relation to the region of formation, we combine the airborne observations with 10 d backward trajectories to identify the location of cirrus formation and the cirrus type, i.e. in situ or liquid origin cirrus, depending on whether there is only ice or also liquid water present in the cirrus history, respectively. The cirrus formed and measured at mid-latitudes (M–M) have a particularly high ice number concentration and low effective diameter. This is very likely a signature of contrails and contrail cirrus, which is often observed in the in situ origin cirrus type. In contrast, the largest effective diameter and lowest number concentration were found in the cirrus formed and measured at high latitudes (H–H) along with the highest relative humidity over ice (RHi). On average, in-cloud RHi was above saturation in all cirrus. While most of the H–H cirrus were of an in situ origin, the cirrus formed at mid-latitudes and measured at high latitudes (M–H) were mainly of liquid origin. A pristine Arctic background atmosphere with relatively low ice nuclei availability and the extended growth of few nucleated ice crystals may explain the observed RHi and size distributions. The M–H cirrus are a mixture of the properties of M–M and H–H cirrus (preserving some of the initial properties acquired at mid-latitudes and transforming under Arctic atmospheric conditions). Our analyses indicate that part of the cirrus found at high latitudes is actually formed at mid-latitudes and therefore affected by mid-latitude air masses, which have a greater anthropogenic influence.